Luteinizing hormone induces ovulation via tumor necrosis factor α-dependent increases in prostaglandin F(2α) in a nonmammalian vertebrate - Crespo, Diego (Sci Rep, 2015)
Ovulation is induced by the preovulatory surge of luteinizing hormone (LH) that acts on the ovary and triggers the rupture of the preovulatory ovarian follicle by stimulating proteolysis and apoptosis in the follicle wall, causing the release of the mature oocyte. The pro-inflammatory cytokine tumor necrosis factor α (TNFα) and prostaglandin (PG) F(2α) (PGF(2α)) are involved in the control of ovulation but their role mediating the pro-ovulatory actions of LH is not well established. Here we show that Lh induces PGF(2α) synthesis through its stimulation of Tnfα production in trout, a primitive teleost fish. Recombinant trout Tnfα (rTnfα) and PGF(2α) recapitulate the stimulatory in vitro effects of salmon Lh (sLh) on contraction, proteolysis and loss of cell viability in the preovulatory follicle wall and, finally, ovulation. Furthermore, all pro-ovulatory actions of sLh are blocked by inhibition of Tnfα secretion or PG synthesis and all actions of rTnfα are blocked by PG synthesis inhibitors. Therefore, we provide evidence that the Tnfα–dependent increase in PGF(2α) production is necessary for the pro-ovulatory actions of Lh. The results from this study shed light onto the mechanisms underlying the pro-ovulatory actions of LH in vertebrates and may prove important in clinical assessments of female infertility.